A LEGAL PORTRAIT OF HEALTH COMMUNICATION: RESPONSIBLE HEALTH INFORMATION DELIVERY, PATIENT PROTECTION, AND THE ROLE OF MEDIA IN PUBLIC EDUCATION - Hotmaria Hertawaty Sijabat; Andreas Harry; Gunawan Widjaja (Jurnal Komunikasi, 2025)
The legal portrait of health communication is an important study that highlights aspects of responsible health information delivery, protection of patient rights, and the role of the media in public education. The delivery of health information must be based on strict ethical and legal standards, so that the public gets accurate and reliable data. In addition, the law also serves to protect patients by ensuring the confidentiality of health information and guaranteeing correct and transparent information. The media, as the main means of information dissemination in the digital era, plays a crucial role in improving public health literacy and preventing the spread of hoaxes that can be misleading. With a synergistic interaction between information providers, legal regulations, and the media, effective health communication can be achieved, benefiting the welfare of society at large